Problems of Electrical Engineering Department Students of Polytechnic of Raflesia in Speaking English in Group Presentation - Desti Ariani (Universitas Bengkulu, 2020)
This descriptive study was conducted to investigate the problems faced by Electrical Engineering Department Students of Polytechnic of Raflesia in speaking English in group presentation. 27 students of the second semester were purposefully taken as the sample for they have been involved in some of group presentations since they were still in the first semester. Observation checklist and field note were used to collect the data on students’ problems. The interview then was conducted to those who were evidenced to have English speaking problems seen from the data perceived earlier from observation. The study revealed that the dominant linguistic problem of the students in speaking English was their poor pronunciation. The result of the data analysis showed that it was 16 students (59, 26%) among 27 students who were evidenced to have this pronouncing problem. Meanwhile the major psycholinguistic problem was the students’ anxiety in using the language. It was 15 students (55, 56%) who were admitted to have this problem.